Innovative crack-healing hybrid fiber reinforced engineered cementitious composite. (30th September 2017) - Ali, M.A.E.M.; Nehdi, M.L.
Highlights: Innovative SMA-PVA engineered cementitious composite was pioneered. The composited is endowed with strain recovery owing to SMA fibers. The new composite offers superior tensile, flexural and toughness behavior. Structural safety could be enhanced using the new composite. Abstract: An innovative hybrid engineered cementitious composite with crack-healing capability is pioneered in this study. The mechanical properties of this composite, which incorporates short randomly dispersed polyvinyl alcohol (PVA) and shape memory alloy (SMA) fibers were investigated. Results show that a combination of PVA and SMA fibers significantly enhanced the tensile and flexural capacity of the ECC by 59% and 97%, respectively compared to that of a conventional ECC made with 2% PVA fiber alone. No further improvement in mechanical behavior was achieved beyond a certain fiber dosage due to increased porosity and fiber clustering. In spite of the damage incurred by coexisting PVA fibers due to heat treatment, cracked SMA-ECC specimens were self-healed upon heat treatment owing to the self-centering capability of SMA fibers. The findings of this research highlight the prospect to engineer novel cementitious composites with eminent mechanical behavior to mitigate damage mechanisms and enhance safety of infrastructure critical for national security importance.